Athletic constructivism & kinesthetic inquiry. An educational theory-based method for coaching track and field - Goffena, J.; Haley MacKenzie, A. (Techniques Magazine, 2012)
In science education, the paradigm is changing where science teachers are encouraged to focus more on how students learn and less on the delivery of static information. The goal is for the teacher to provide opportunities for the students that helps them "uncover" the text, instead of covering it (Duckworth, 2006). This method, called scientific inquiry, is based on the constructivist model that provides students with the chance to understand a subject, rather than merely retaining knowledge. This article will provide a different lens to coaching by infusing constructivist approaches gleaned from science education research. The question"How can science education inform the coaching experience?" is answered.